Coupled HF azimuthal waves in magnetoactive waveguide partially filled by current-carrying plasma - Girka, O.I.; Girka, I.O.; Girka, V.O.; Pavlenko, I.V. (Вопросы атомной науки и техники, 2006)
Coupled surface extraordinarily polarized waves and bulk ordinarily polarized waves are proved to propagate along azimuthal direction in the cylindrical metal waveguide that is partially filled by cold magneto-active plasma in the frequency range above upper hybrid resonance. Their interaction and linear conversion is investigated under the condition of an external magnetic field with both axial and azimuthal components application.